The Use of Artificial Intelligence Chatbots in Teaching Foreign Languages as an Innovative Interactive Technology - Rudnik, Yuliia (Educological discourse, 2024)
The article explores the didactic potential of the use of artificial intelligence technologies, specifically chatbots, in teaching foreign languages. It delves into the advantages of integrating chatbots into the foreign language learning process, based on the experience of teaching the “Foreign Language (English)” discipline to the first-year students of the 024 Choreography speciality of the Faculty of Musical Art and Choreography, and the 022 Design speciality of the Faculty of Fine Arts and Design at Borys Grinchenko Kyiv Metropolitan University. While highlighting the educational benefits and interactive nature of chatbots, it also addresses their drawbacks and suggests methods to mitigate potential negative consequences such as academic integrity violations and copyright issues like plagiarism. The article offers advice on appropriate usage and adheres to relevant policies. Moreover, it provides practical examples of using chatbots in teaching foreign languages based on the use of Mizou software. The study is a theoretical research article employing general scientific analytic methods such as synthesis, generalization, and systematization. It includes a review of the related literature on the stated problem as well as an overview of the empirical experience of the introduction of chatbots in the “Foreign Language (English)” discipline. The paper defines the didactic potential of the Mizou by providing a general overview of the functions and modes of the aforementioned software and drives a reader through the personalized chatbot process of creation and customization. The provided research highlights the necessity of further investigation of the implementation of artificial intelligence chatbots as an innovative interactive technology with significant didactic potential that should be empirically tested and analysed.